A comprehensive analysis of the impact of biofuels on the performance and emissions from compression and spark-ignition engines. (August 2015) - Di Iorio, Silvana; Mancaruso, Ezio; Sementa, Paolo; Vaglieco, Bianca Maria
The compression ignition and small displacement spark-ignition engines play an important role in the urban air pollution. In particular, vehicles equipped with compression ignition engines are widely used because of their higher performance and fuel efficiency with respect to the spark-ignition ones. Nevertheless, spark-ignition engines with low displacements are even more wide-spreading because of the lower fuel consumption and emissions. They are also used for two-wheeled vehicles, whose easier navigation makes them widely used in heavily congested areas. Their contribution on urban pollution is worsened by the fact that these vehicles have to comply with the Euro 3 standard; light vehicles have, instead, to fulfill the more restrictive Euro 6, which for the compression ignition and gasoline direct injection engines indicates for particle emissions also a number-based regulation. This article aims to characterize the effects of biofuels on engine emissions and performance of compression ignition and spark-ignition engines. The investigation was carried out on different class of engines. Direct injection and a port fuel injection spark-ignition engines fueled with ethanol and its blends, 10 v/v%, 50 v/v% and 85 v/v% of ethanol in gasoline. The compression ignition engine was equipped with a common rail injection system and was fueled with pure rapeseed methyl ester, representative of fatty acid methyl ester, and its blends in diesel, 20 v/v% and 50 v/v%. The gaseous emissions and the particle concentration were measured at the exhaust by means of conventional instruments. Particle size distribution function was measured in the range from 5.6 to 560 nm by means of an engine exhaust particle sizer. A comprehensive characterization of the particulate carbon was performed by means of optical diagnostics in the combustion chamber. In particular, two-dimensional images of flame evolution were detected and processed by two-color pyrometry technique to assess the in-cylinder soot formation and oxidation processes. For both the investigated spark-ignition and compression ignition engines, the use of biofuels shows a partial increase in the specific fuel consumption and a reduction of the soot particles emission. Nevertheless, a further effort on engine technology should be paid to balance the mass with the size and number of the particles.